Impact of salinity on macro-and micronutrient uptake in mango (Mangifera indica L. cv. Osteen) with different rootstocks - Duran Zuazo, V.H.=700 1 Martinez-Raya, A.; Aguilar Ruiz, J.; Franco Tarifa, D.
(Es, En)
ilus., 66 ref.
Keywords: MANGIFERA INDICA; NUTRIENTES MINERALES; ESTRES; SALINIDAD; CULTIVOS; ESPAÑA; ESTRES SALINO; CULTIVOS SUBTROPICALES